Archaeological Heritage Protection System in Lithuania: Changes in Legislation During the Last Decade - Augustinavičius, Renaldas; Poškienė, Justina (Archaeologia Lituana, 2016)
The last decade in the field of cultural and archaeological heritage protection was determined by the Law on Protection of Immovable Cultural Heritage, which came into force in 2005. The most notable changes are observed in: 1) accounting, assessment of valuable properties and listing of archeological heritage objects 2) legislation of requirements of archaeological heritage protection 3) regulation of archaeological excavations.Approx. 2,800 objects (individual objects, complex objects and sites) are listed in the state Register of Cultural Property. The majority are hill-forts (approx. 30%), burial mounds and their places (approx. 23%), burial grounds and old cemeteries (approx. 23%), ancient settlements (approx. 15%), and the rest are cultural layers of old towns, manor places, castle places and other types of archaeological sites (e.g. ancient production sites). Additionally, there are more than 450 heritage objects (mostly buildings), which are also assessed as bearing archaeologically valuable properties. Archaeological heritage comprises approx. 17% of immovable cultural values, listed in the state Register of Cultural Property.During the last decade, accomplishment of assessment of valuable properties and listing of archaeological heritage objects was planned. Thus, the coherency of heritage protection restrictions applied for land property use had to be guaranteed. For this purpose, immovable cultural assessment councils were established. Immovable cultural property is registered (listed) after an assessment council decides that a property is in the need of legal protection. The significance of immovable cultural property and the valuable properties of objects or sites of cultural heritage are determined and the boundaries of territories are defined by the immovable cultural heritage assessment councils as well. The specialised assessment council for archaeological heritage was established next to the Department of Cultural Heritage in 2012.Data exchange between the Register of Cultural Property and the Real Estate Register should be identified as an extremely important turning point in making heritage information on restrictions of land use available for cultural heritage managers and users.Nevertheless, concentration of state administrative and technical resources mainly on preparation of new documentation type for already listed heritage objects (the act of assessment council) led to the stagnation of accounting – identifying, inventorying and assessment – of new archaeological heritage objects. It also hindered elaboration of archaeological heritage management strategies from “heritage object” towards “heritage process”. Integration of the latest archaeological data into the general heritage management process (e.g. identification of new archaeological heritage objects, determination of valuable properties and values of archaeological heritage and application of relevant conservation strategies, explaining meaning of archaeological heritage preservation for descendant and non-local communities, etc.) is still weak. Re-orientation of the archaeological heritage protection perspective from the “object” towards its manager or user, as well as community in general, should be seen as the main heritage management task for the next decade.Aiming at differentiation of administrative load, heritage protection procedure was divided into two stages: initial protection of immovable cultural heritage and declaration of an object of cultural heritage protected. Special territorial planning documentation had to be prepared in order to implement the second stage of protection. The extent of resources needed for preparation of this documentation type was not initially estimated and in 2013 the procedure was turned back to the system valid in 1995–2005: a procedure of declaration of an object of cultural heritage protected for an individual and ordinary complex objects is introduced by typical or individual protection regulations, for cultural heritage sites – by special territorial planning documents.Archaeological excavations/destructive research – or “protection through documentation” – became the main form of archaeological heritage protection during the last decade. As the contract archaeology system was developed, great attention was paid to excavations’ quality control procedures. In 2011, Heritage Maintenance Regulation PTR 2.13.01:2011 „Archaeological Heritage Maintenance“ was adopted. Thus requirements for archaeological heritage excavation (where and how archaeological excavations should be conducted) became a legal norm for the first time in the history of heritage protection in Lithuanian. Legal regulations adjusted essential conditions of competition for contract archaeologists as well. Nevertheless, objectification of criteria of archaeological research is modeling the situation “of typical archaeological excavations”, and thus in the professional community raises discussions concerning the scope of scientific information obtained during the archaeological excavations.Heritage Maintenance Regulation also demands to protect archaeological heritage constructs in situ. Seeking for successful implementation of this goal, the necessity of archaeological heritage identification and research in the earliest stages of development works should be guaranteed. Attempts for identifying and coordination of various interests towards archaeological heritage should be actively applied in order not only to preserve material archaeological relics, but also to interpret and present archaeological heritage values for the society in general.
Keywords: Archaeological Heritage; Immovable Cultural Heritage; Protection of Archaeological Heritage; Assessment of Valuable Properties; Archaeological Excavations